Functional impairment of knee muscles after walking with backpack load: a systematic review - Fabio Alves Machado; Renan de Siqueira Csuka; Samir Ezequiel da Rosa; Runer Augusto Marson; Eduardo Camillo Martinez; Victor Manuel Machado de Ribeiro Reis (Termedia Publishing House, 2024)
To review the available literature on the acute and temporal effects of backpack load carriage on knee muscle force production post-walking. Data sources: The databases were PubMed, Lens, ScienceDirect, Scopus, BVS, and EBSCO. Study selection: The eligibility criteria were: sample aged between 18 and 45 years old, backpack load carriage walking, knee flexor and/ or extensor muscle strength measurement comparing post-walking with pre-walking or with no-load walking; articles that reported at least one acute response, and/or temporal response; randomised controlled trials and prospective cohort studies that have a longitudinal design that compared two or more groups, or one group with a test and re-test output described and written in English. This systematic review was conducted in accordance with the PRISMA 2020 Statement. We used the Joanna Briggs Institute Critical review tool for randomised controlled trials and prospective cohorts to assess the methodological quality of the studies. A total of 1004 records were screened, and five studies were included in the review. Data extraction: Participant details, study design, load carriage system, load carriage conditions, walking conditions, and method and instrument used to measure strength. Conclusions: The acute and temporal neuromuscular impairments are load-dependent and are independent of the intervention performed. Acute impairments seem to occur due to a decreased ability to modulate motor output rapidly and accurately, and temporal impairment by eccentric motor activity increased by the external load. Carbohydrate or whey protein accelerates the recovery of neuromuscular function after prolonged load carriage occurs in isometric strength, but not in isokinetic strength.